Preparation and characterization of MG30 with antioxidant additive as polymer electrolytes / Ahmad Fairoz Aziz - Aziz, Ahmad Fairoz (2019)
This work is focused on obtaining high conducting solid polymer electrolytes (SPEs) based on treated 30% methyl grafted natural rubber (TMG30). MG30 is easily degraded and deteriorated due to the presence of unsaturated hydrocarbon (C=C) in the natural rubber backbone. 30% methyl grafted natural rubber (MG30) was treated with N-(1,3-dimethylbutyl)-N’-phenyl-p-phenylenediamine (6PPD) as antioxidant to retard MG30 degradation prior to use as polymer host. Lithium trifluoromethanesulfonate (LiTf) was used as dopant salt. All samples were prepared by solution casting technique. 0.5 wt. % of 6PPD was found to be the best composition to retard MG30 thermal degradation. Fourier transform infrared spectroscopy (FTIR) study was carried out to confirm the polymer salt complexation. The percentage of free ion of TMG30 with 40 wt. % of LiTf was found to be the highest among all the prepared samples. The conductivity study showed that the samples with TMG30 with 40 wt. % LiTf have the highest ionic conductivity with value of 1.59E-04 Scm-1 at room temperature. Differential scanning calorimetry (DSC) studies demonstrated no significant changes in glass transition temperature (Tg) value between MG30 and TMG30 electrolytes. However, X-ray diffraction (XRD) confirms TMG30 electrolytes were more amorphous than MG30 electrolytes. The temperature dependence conductivity showed that the ion transport mechanism of both electrolytes obeys Vogel-Tamman-Fulcher (VTF) behaviour. The study on 6PPD effect in combating thermal degradation of MG30 electrolytes were done by using heat treatment conductivity study to obtain the electrolytes relaxation time (To). The different between MG30 and TMG30 electrolytes To revealed that the TMG30 electrolytes is more resistance to physical aging by 5.6 to 6.6 hour for 35 and 40 wt. % respectively. The transference number (tn) confirmed that the charge carrier of both electrolytes were predominantly ions. The linear sweep voltammetry test showed that both electrolytes obtained window stability of 3.1 V. The introduction of 6PPD in the electrolytes does not provide significant effect in the electrolytes window stability.